2020
DOI: 10.15547/bjvm.2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic analysis of ovine herpesvirus-2 in sheep and goats of Al-Qadisiyah Province

Abstract: This study aimed to identify ovine herpesvirus 2 (OHV-2) infections in sheep and goats in Al-Qadisiyah Province of Iraq, using molecular and phylogenetic methods. Nasal discharge swabs were collected from 60 sheep and 60 goats from 3 different animal sale bars. The samples were subjected to semi-nested-polymerase chain reaction (PCR), sequencing, and phylogenetic tests involving OHV-2 tegument protein gene (OHV-2T). The results of the semi-nested PCR showed the presence of OHV-2 in all 60 (100%) sheep and 52 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Based on the results of BLAST and phylogenetic analysis, the sequences obtained in this study showed approximately 98-100% similarity to other published sequences of the ORF75 tegument protein gene internationally. These ndings support other researchers' ndings that there is no major difference between OvHV-2 sequences globally [14,19,31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on the results of BLAST and phylogenetic analysis, the sequences obtained in this study showed approximately 98-100% similarity to other published sequences of the ORF75 tegument protein gene internationally. These ndings support other researchers' ndings that there is no major difference between OvHV-2 sequences globally [14,19,31].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Li et al ( 2001) indicated that OvHV-2 can infect fetuses during pregnancy [27], as reported by Pekmez et al [24]. The ndings for the virus in different age groups suggest that the virus is endemic to the area, as reported by Mananguit et al in Philippines [31] and Khudhair in Iraq [14].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In sheep, OvHV-2 virus DNA was detected in 37 of the whole blood samples (62.7%), 7 of the internal organ samples (25.9%), 3 of the fetus samples(16.6%), and 45.1% of all sheep samples. Similarly, previous studies have showed that prevalence of OvHV-2 in goats lower than sheep (Wiyono 1999;Banumathi et al 2008;Khudhair et al 2020).…”
Section: Discussionmentioning
confidence: 58%